Caminhos, possibilidades e perspectivas da EJA EPT na rede federal de ensino no estado do Rio Grande do Sul (RS) - Raimundo, Fabiana Ilha (2022)
The study, PATHS, POSSIBILITIES AND PERSPECTIVES OF EJA EPT IN THE FEDERAL EDUCATION NETWORK IN THE STATE OF RIO GRANDE DO SUL (RS), is presented as a dissertation of the Academic Master in Professional and Technological Education of the Industrial Technical College of the Federal University of Santa Maria (CTISM/UFSM). It is associated with the research line LP1: Policies and Management in Professional and Technological Education and with the research group TransformAção – Group of Studies and Research in Public Policies and Pedagogical Work in Professional Education. The study sought to analyze indicators, characteristics and possibilities of EJA-EPT in RS. Conceptions outlined by normative instruments and social indicators that are available on public websites were investigated. For this study, federal public institutions that offer EJA EPT were researched: three Federal Institutes of Education, Science and Technology named by Farroupilha, Rio Grande do Sul and Sul-rio-grandense and a federal technical school, Colégio Técnico Industrial de Santa Maria . With that, the problematization of this study arose: What are the indicators, characteristics and possibilities of the EJA EPT policy of the Federal Network (RF) of education in RS from the PNE 2014-2024? The specific objectives were thus established: to build the historicity of the EJA and EJA EPT policy at the national level, to quantitatively analyze the offer and indicators of EJA EPT in RS and to present challenges and possibilities of the EJA EPT policy in RS. The methodology was presented by the mixed method approach, as it incorporates qualitative and quantitative elements. It was classified as documentary and bibliographical research, as it involves studying the characteristics of a population. For that, data were produced by means of legislation and websites that presented educational and historical indicators. The analysis was carried out using descriptive statistics. The results of this study indicated that both the offer of courses and the percentage of enrollees has not been very expressive. Enrollments did not reach the percentage of 10% by current legislation and Target 10 of the PNE is very far from being achieved. In addition, it was possible to conclude that the indicators and characteristics of the courses demonstrate that the path to the implementation of the public policy of EJA EPT is still being built, and the challenges and perspectives for the improvement of this modality must be planned by the Management of these institutions and promoted by the Ministry of Education, as seems to be happening with the offer contained in Public Notice 17/22, so that it becomes, finally, a State policy. It is also concluded that EPT EJA needs attention because even with a specific goal in the current PNE it is not possible to present it as a consolidated public policy before society.